Morphological and molecular identification of Particolored bat (Vespertilio murinus) in South Korea: A first record - Bong Kyun Kim; Jeong Hun Shim; Sun Sook Kim; Soo Hyung Eo (Biodiversity Data Journal)
BackgroundVespertilio murinus belong to the genus Vespertilio and are widely distributed in Europe, the Middle East and Northeast Asia, Recently, the presence of the V. murinus has been confirmed in Japan, suggesting the possibility of its habitation on the Korean Peninsula. However, ecological information regarding its presence in the Korean Peninsula is extremely limited.New informationIn an urban area of Sejong City, South Korea, a bat within the genus Vespertilio was rescued by personnel of the Chungnam Wild Animal Rescue Center. The bat, which was believed to have been hibernating on an exterior wall of a building, was initially identified as Vespertilio sinensis. However, the confirmed presence of two pairs of nipples raised the possibility that the bat was a specimen of V. murinus. The measurement of the forearm length (FAL) of this bat was 45.67 mm, which is within the 95% confidence interval of the previously reported FALs of V. murinus. Additionally, the results of mtDNA sequence analysis indicated that the rescued bat could be differentiated from the closely-related species V. sinensis with respect to the sequences of 13PCGs, COI, Cytb and ND1. Finally, phylogenetic analysis revealed that this bat clustered in a clade with previously described V. murinus. Collectively, these findings provided convincing evidence to indicate that the rescued individual was a V. murinus, marking the first recorded observation of this species in South Korea.